2018
DOI: 10.1161/jaha.117.007572
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3‐Kinase–DNA Methyltransferase 1–miR‐1281–Histone Deacetylase 4 Regulatory Axis Mediates Platelet‐Derived Growth Factor–Induced Proliferation and Migration of Pulmonary Artery Smooth Muscle Cells

Abstract: BackgroundPlatelet‐derived growth factor BB, a potent mitogen of pulmonary artery smooth muscle cells (PASMCs), has been implicated in pulmonary arterial remodeling, which is a key pathogenic feature of pulmonary arterial hypertension. Previous microRNA profiling in platelet‐derived growth factor BB–treated PASMCs found a significantly downregulated microRNA, miR‐1281, but it has not been associated with any cellular function, and we investigated the possibility.Methods and ResultsReal‐time quantitative revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 86 publications
(140 reference statements)
0
18
0
Order By: Relevance
“…Apart from the histone deacetylase 4 (HDAC4) gene, that has been recently shown as a direct target of miR-1281 in pulmonary artery smooth muscle cells (54), no other targets of miR-1281 have been identified yet. Our in vitro results from human ARPE-19 retinal cells show that the extracellular release of miR-1281 following high glucose treatment significantly exceeded the release under low glucose conditions, and this behavior only partially reflected that of endothelial HUVEC cells, in which miR-1281 was also significantly reduced in the intracellular environment, although to a lesser extent than in ARPE-19 cells, but was unchanged in the extracellular medium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the histone deacetylase 4 (HDAC4) gene, that has been recently shown as a direct target of miR-1281 in pulmonary artery smooth muscle cells (54), no other targets of miR-1281 have been identified yet. Our in vitro results from human ARPE-19 retinal cells show that the extracellular release of miR-1281 following high glucose treatment significantly exceeded the release under low glucose conditions, and this behavior only partially reflected that of endothelial HUVEC cells, in which miR-1281 was also significantly reduced in the intracellular environment, although to a lesser extent than in ARPE-19 cells, but was unchanged in the extracellular medium.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, only few studies have been published in which authors had identified miR-1281 as a potential biomarker in human diseases. Among these disease states were abdominal aortic aneurysm ( 53 ), coronary heart disease and pulmonary arterial hypertension ( 54 ), chronic nephropathy ( 55 ), immune thrombocytopenic purpura ( 56 ), and malignant pleural mesothelioma ( 57 ). Our findings in the present work are consistent with these studies, implicating miR-1281 as a potential biomarker to track disease progression or aid in disease diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…2C]. MiRNA-1281 suppresses proliferation and migration in pulmonary artery smooth muscle cells, likely through targeting histone deacetylase 4 (HDAC4) (Li et al 2018b). In osteosarcoma, miR-1281…”
Section: Discussion____________________________________________________mentioning
confidence: 99%
“…All the obtained constructs were verified by DNA sequencing. The luciferase activities were detected as described previously [212223]. Chemically synthesized miR-181a mimic and the corresponding negative control (NC) were provided by Ruibobio (Guangzhou, China).…”
Section: Methodsmentioning
confidence: 99%